Primary Malignant Melanoma Of The Parotid Gland Combined 18F-FDGPET/CT And Immunochemical Diagnosis with Literature Review - Darouichi Mohammed (Journal of Digestive Disorders And Diagnosis, 2016)
Summary Primary malignant melanoma arising from the parotid gland is extremely rare and only sporadic cases have been described. This entity is characterized by delayed diagnosis, poor prognosis and controversial pathogenesis. We report a case of primary malignant melanoma of the parotid gland in a 54-year-old man. The initial diagnosis, made by fine needle aspiration cytology, was malignant tumor without precision. Radical parotidectomy was performed. Diagnosis of primary melanoma of the parotid gland was confirmed by immunochemical analysis revealing positive staining for S-100, HBA-45 and Melan A. Computed Tomography and whole-body 18F-FDGPET/CT image were made to evaluate metabolic and morphologic characteristics of the primary melanoma, to identify potential systemic metastasis at early stage and to exclude primary melanoma elsewhere in the body. The clinical, pathological, immunohistochemical and the role of combined FDG PET/CT features of this lesion are discussed compared to a literature review.
Keywords: parotid gland